Histone Deacetylase 1/mSin3A Disrupts Gamma Interferon-Induced CIITA Function and Major Histocompatibility Complex Class II Enhanceosome Formation - Zika, Eleni (American Society for Microbiology, 2003)
The class II transactivator (CIITA) is a master transcriptional regulator of major histocompatibility complex class II (MHC-II) promoters. CIITA does not bind DNA, but it interacts with the transcription factors RFX5, NF-Y, and CREB and associated chromatin-modifying enzymes to form an enhanceosome. This report examines the effects of histone deacetylases 1 and 2 (HDAC1/HDAC2) on MHC-II gene induction by gamma interferon (IFN-γ) and CIITA. The results show that an inhibitor of HDACs, trichostatin A, enhances IFN-γ-induced MHC-II expression, while HDAC1/HDAC2 inhibits IFN-γ- and CIITA-induced MHC-II gene expression. mSin3A, a corepressor of HDAC1/HDAC2, is important for this inhibition, while NcoR, a corepressor of HDAC3, is not. The effect of this inhibition is directed at CIITA, since HDAC1/HDAC2 reduces transactivation by a GAL4-CIITA fusion protein. CIITA binds to overexpressed and endogenous HDAC1, suggesting that HDAC and CIITA may affect each other by direct or indirect association. Inhibition of HDAC activity dramatically increases the association of NF-YB and RFX5 with CIITA, the assembly of CIITA, NF-YB, and RFX5 enhanceosome, and the extent of H3 acetylation at the MHC-II promoter. These results suggest a model where HDAC1/HDAC2 affect the function of CIITA through a disruption of MHC-II enhanceosome and relevant coactivator-transcription factor association and provide evidence that CIITA may act as a molecular switch to modulate MHC-II transcription by coordinating the functions of both histone acetylases and HDACs.